Impact of COVID-19 on the Neurosurgical Resident Training Program: An Early Experience - Omer, Mazin; Al-Afif, Shadi; Machetanz, Kathrin; Bettag, Christoph; Tatagiba, Marcos; Rohde, Veit; Krauss, Joachim K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background The present study evaluates the impact of COVID-19 pandemic restrictions during the first lockdown period in spring 2020 on the neurosurgical resident training program, and provides constructive approaches to deal with such situations.Methods A concurrent embedded mixed methods design was used. Qualitative data were collected through in-depth interviews from all neurosurgical residents at three university hospitals in Germany. Concurrently, quantitative data of the number of performed surgeries, outpatient visits, and the usage of telemedicine in the period from October 2019 to July 2020 were collected and analyzed accordingly.Results During the period of COVID-19 pandemic restrictions in spring 2020, there was a marked reduction in the number of surgeries performed by neurosurgical residents, from an average of 41.26 (median 41) surgeries per month to 25.66 (median 24) per month, representing a decrease of 37.80%. The decrease in the operations was concerning mainly spinal and functional surgery. Outpatient visits were reduced significantly, with a concurrent fivefold increase in the usage of telemedicine. General and pediatric neurosurgery outpatient clinics were the most affected. However, although surgical exposure was reduced during the lockdown phase, neurosurgical residents focused on conducting research and improving theoretical knowledge. Nevertheless, the global uncertainties caused by COVID-19 generated notable psychological stress among some residents.Conclusions The COVID-19 pandemic restrictions significantly affected the neurosurgical training program. Innovative solutions need to be developed to increase teaching and research capacities of neurosurgical residents as well as to improve surgical skills by installing surgical skill laboratories or similar constructs.
Keywords: corona virus; COVID-19; neurosurgery; residency program; education